Sequence stratigraphy, palaeogeography, and coal accumulation in a gently sloping paralic basin: A case study from the Carboniferous–Early Permian Wuwei Basin, northwestern China. (16th January 2018) - Shen, Wenchao; Shao, Longyi; Tian, Wenguang; Sun, Bin; Chen, Gang; Chen, Fei; Tian, Ye; Lu, Jing
Abstract : The Wuwei Basin is one of the major coal‐ and hydrocarbon‐bearing basins in northwestern China. Depositional environments, sequence stratigraphy, and palaeogeography of the Carboniferous to Early Permian coal measures in the Wuwei Basin were studied based on the data from outcrop sections and boreholes cores. The coal accumulation model is established within the sequence‐stratigraphic context. Fourteen lithofacies were recognized with the lithologies ranging from conglomerates, sandstones, siltstones, mudstones, carbonates, to coals, which are arranged into five facies associations representing delta, tidal flats, barrier and lagoon, littoral and associated strand‐plain, estuary, and carbonate ramp environments. These facies associations collectively revealed an overall marine‐continental transitional basin setting. The key sequence bounding surfaces, such as the regional unconformity, the basal surface of incised valley fills, and the surface that mark the facies reversal from regression to transgression, have been identified. Based on these surfaces, the Carboniferous to Early Permian in the Wuwei Basin were subdivided into seven third‐order sequences. The distribution of lithofacies and depositional facies in borehole sections, outcrop sections, and three correlation cross sections was investigated, and the sequence‐based palaeogeographic maps were reconstructed. It is inferred from the coal thickness and palaeogeographic maps that the most favourable coal accumulation environments were tidal flat and barrier–lagoon, followed by delta. The sequence stratigraphic framework controls the vertical horizons of the coal seams, whereas the palaeogeographic units determine the lateral development of the coal seams. Tidal flat, barrier–lagoon, and delta in the late transgressive systems tract and early highstand systems tract are the most favourable coal accumulation palaeogeographic units. The main coal accumulation centres were mainly distributed in the Yingpan Sag in the south of the basin, followed by the Ermahu Sag in the north of the basin.